Choledochal Cysts with Chronic Pancreatitis in Adults: Report of Two Cases with a Review of the Literature - Gouda, Biswanath P; Desai, Devendra C; Abraham, Philip; Joshi, Anand; Shah, Sudeep R (JOP. Journal of the Pancreas, 2010)
Context Choledochal cysts, rarely present with chronic calcific pancreatitis. We report two patients with choledochal cysts who had concomitant chronic pancreatitis. Case report #1 A 27-year-old female with a history of recurrent abdominal pain, fever and jaundice presented with a type I choledochal cyst with calcifications in the uncinate process of the pancreas on CT scan. Her magnetic resonance cholangiopancreatogram (MRCP) revealed calcifications in the region of the uncinate process of the pancreas, the presence of a type I choledochal cyst with dilatation of the right and left hepatic ducts at their confluence suggesting an anomalous pancreaticobiliary ductal junction. She underwent choledochal cyst excision with a Roux-en-Y hepaticojejunostomy. Case report #2 A 35-year-old male with colicky abdominal pain of four months duration whose CT scan was suggestive of an atrophic pancreas with a 1 cm dilatation of the pancreatic duct and a calculus in the pancreatic duct near the ampulla. MRCP showed significant atrophy of the pancreas with an isointense filling defect seen in the pancreatic duct at its distal end near the ampulla. A diagnosis of chronic calcific pancreatitis with type I choledochal cyst was made. He underwent choledochal cyst excision with a cholecystectomy, hepaticojejunostomy (end-to-side) and side-to-side pancreaticojejunostomy. Conclusion Chronic calcific pancreatitis is a rare occurrence in patients with choledochal cysts and only six cases have been reported in the literature. Our two patients with choledochal cysts associated with chronic pancreatitis were treated surgically. Image: Type Ic choledochal cyst with a dilated pancreatic duct and filling defect seen proximal to the ampulla